Cystic echinococcosis in wild boars (Sus scrofa) from southern Italy: Epidemiological survey and molecular characterization. (August 2019) - Sgroi, Giovanni; Varcasia, Antonio; Dessi, Giorgia; D'Alessio, Nicola; Tamponi, Claudia; Saarma, Urmas; Laurimäe, Teivi; Kinkar, Liina; Santoro, Mario; Caputo, Vincenzo; Sarnelli, Paolo; Fusco, Giovanna; et al.
Abstract: Cystic Echinococcosis (CE) caused by Echinococcus granulosus sensu lato (s.l.) is one of the most important parasitic zoonotic diseases in the world and it represents an important public health and socio-economic concern. In the Mediterranean basin, CE is widespread and it is endemic in Italy, with major prevalence in southern areas. Several studies have investigated CE in domestic pigs, however, such data in wild boars are scant. In the last decades the wild boar population in Italy has increased and this ungulate could play an important role in the spreading of CE in the wild. Here we report on the prevalence and fertility rate of hydatid cysts in wild boars that were shot during two hunting seasons (2016–2017) in the Campania region of southern Italy. For each animal, a detailed inspection of the carcass and organs (lungs, liver and spleen) was performed and when cysts were found, their number, morphology and fertility were determined by visual and microscopic examination. Cysts were classified morphologically as fertile, sterile, caseous and calcified. Protoscoleces and germinal layers were collected from individual cysts and DNA was extracted to identify different strains/genotypes of E. granulosus s.l. Out of a total of 2108 wild boars 93 (4.4%) were found positive for CE. Infected animals were 45 males and 48 females, aged between 1 and 8 years. The average number of cysts per wild boar was 1.3 (min 1 - max 13). The total number of cysts collected was 123, of which 118 (95.9%) in the liver, 4 (3.3%) in the lungs and 1 (0.8%) in the spleen. Of all analyzed cysts, 70 (56.9%) were fertile and 53 (43.1%) sterile/acephalous. The presence of fertile cysts in 19.4% of CE-positive animals is noteworthy. Overall, molecular diagnosis showed 19 wild boars infected with the pig strain (G7). Graphical abstract: Image 1 Highlights: A survey on CE on 2.108 wild boars from southern Italy was performed. The prevalence of CE was 4.4% with fertility rate of 1.0%. Echinococcus granulosus G7 genotype was isolated.